Impact of increasing transmission capacity for a massive integration of renewable energy on the energy and environmental value of distributed generation. (January 2022) - Oliva H., Sebastian; Muñoz, Juan; Fredes, Felipe; Sauma, Enzo
Abstract: Distributed generation (DG) can offer significant value to power systems by reducing some of the energy and emission marginal costs of centralized generation. These costs can change significantly with the expansion of power systems, especially when renewable energy integration is supported on large new transmission capacity. Accordingly, these cost and price changes could have a potentially large impact on the system value of DG. In this paper, we assess the impact of increasing transmission capacity, for a massive integration of renewable energy, on the energy and environmental system value of solar PV, wind, and energy storage DG. To illustrate this, a case study is presented based on the main Chilean electric power system. We found significant variations in the DG value with different transmission line capacity levels. For instance, just the energy value of PV and storage DG changed up to 43% and 100%, respectively, for line capacity levels growing from 0% (no line) to 200%, in one key transmission line analyzed. This can also represent a strong impact on the revenue of DG projects, generally paid based on this energy value. Furthermore, DG revenue losses can be problematic considering that DG still offers a significant environmental value. Highlights: System energy and emission marginal costs are key drivers of the system DG value. We assess system DG values as a function of transmission line capacity levels. There is a large impact of transmission capacity variations on the system DG values. Transmission and renewable systems can cause significant DG revenue losses. The energy value of PV and storage DG can change up to 43% and 100%, respectively.